Respon Masyarakat Terhadap Perubahan Arah Kiblat Masjid Di Kecamatan Kajang Kabupaten Bulukumba - Ainun Jaria; Halimah B; Anis, Muhammad (Universitas Islam Negeri Alauddin Makassar, 2024)
ABSTRACT The main problem of this research is how the community responds to changes in the direction of the Qibla mosque in Kec Kajang Kab Bulukumba, the subject matter is described in the following sub-problems: 1). What method is used in changing the direction of the Qibla mosque in Kec. Kajang? 2). How did the people of Kec. Kajang respond to the change in the direction of the mosque's qibla? 3). How is the impact of changing the direction of the Qibla mosque on community worship activities in Kajang District? This type of research includes qualitative field research (Field Research). The approach used is the Shari'i approach and the astronomical approach. The primary data source of this study is taken from interviews, secondary data in the form of books and journals related to the Qibla direction. Data collection methods are observation, interviews and documentation. Data processing and analysis techniques are data reduction, data display (data presentation), and verification (conclusion). Data validity testing is data triangulation, observer triangulation, theory triangulation and method triangulation. The results of this study show that 1). The method used in the process of changing the direction of Qibla is by using the method of Compass, Rashdul Qibla and Theodolite. 2). The response of the Kajang community to the change in the direction of Qibla in 3 mosques The response of the Kajang community to the change in the direction of Qibla in 3 mosques is as follows: generally agree that there will be a change in Qibla direction. As for those who reject the change in the direction of Qibla on the grounds that the previous direction of Qibla is correct according to their beliefs. 3). The negative impact of changing the direction of Qibla on community activities or activities is that people feel insecure about these changes, while the positive impact is that the community prefers to pray at home rather than in mosques, people become more diligent in going to mosques. The implications of this study are 1). Facing the Qibla direction is a legal requirement for prayer. So it should be sought so that we are really sure that we have led to the Kaaba by utilizing existing science and technology. 2). The local government through the Ministry of Religious Affairs should be more sensitive in responding to mosques whose Qibla direction is not appropriate or deviated and should also conduct socialization regarding the calibration of the Qibla direction of mosques that are not appropriate or inappropriate. 3). With this research, researchers hope that people can trust more about the existing scientific truth. Keywords: Response, Community, Qibla Direction